2017
DOI: 10.1371/journal.pone.0183070
|View full text |Cite
|
Sign up to set email alerts
|

Muroid rodent phylogenetics: 900-species tree reveals increasing diversification rates

Abstract: We combined new sequence data for more than 300 muroid rodent species with our previously published sequences for up to five nuclear and one mitochondrial genes to generate the most widely and densely sampled hypothesis of evolutionary relationships across Muroidea. An exhaustive screening procedure for publically available sequences was implemented to avoid the propagation of taxonomic errors that are common to supermatrix studies. The combined data set of carefully screened sequences derived from all availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
275
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(317 citation statements)
references
References 75 publications
(145 reference statements)
32
275
2
8
Order By: Relevance
“…Our study corroborates previous molecular studies that fail to find the suggested alliance of Vandeleuria oleracea with Chiropodomys that has been postulated based on dental characters (Musser and Carleton ) and instead strongly supports a sister‐taxon relationship between Chiropodomys and the clade containing Chrotomyini + SOE murines (Schenk et al. ; Steppan and Schenk ). Otherwise, the phylogenetic position of Vandeleuria is not secure in any molecular analysis to date (Schenk et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our study corroborates previous molecular studies that fail to find the suggested alliance of Vandeleuria oleracea with Chiropodomys that has been postulated based on dental characters (Musser and Carleton ) and instead strongly supports a sister‐taxon relationship between Chiropodomys and the clade containing Chrotomyini + SOE murines (Schenk et al. ; Steppan and Schenk ). Otherwise, the phylogenetic position of Vandeleuria is not secure in any molecular analysis to date (Schenk et al.…”
Section: Resultssupporting
confidence: 91%
“…Sequences from additional murid species were chosen primarily from publicly available sources obtained from previous studies (Steppan et al 2005;Rowe et al 2008;Benson et al 2013;Schenk et al 2013;Pagès et al 2016;Rowe et al 2016;P.-H. Fabre, Université Montpellier II, personal communication, August 2017) and were included to place the Philippine murine radiations in the context of murid phylogeny and to provide the best possible divergence date estimates given available fossil data. We selected taxa from subfamilies Gerbillinae, Deomyinae, and Lophiomyinae as outgroups based on their close phylogenetic proximity to Murinae (Schenk et al 2013;Pagès et al 2016;Steppan and Schenk 2017).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Species tree for muroid rodents examined in this study. Modified from (Steppan & Schenk, ). The scale bar measures substitutions per site…”
Section: Methodsmentioning
confidence: 99%
“…This family includes more than 600 species divided into several subfamilies (Carleton & Musser, ). Voles and lemmings represent a well‐defined, monophyletic subfamily (Arvicolinae), although phylogenetic relationships among and within the genera of this subfamily are not yet fully resolved (Bužan, Kryštufek, Hänfling, & Hutchinson, ; Steppan & Schenk, ). Approximately 60 species of voles found in North America, Europe, and northern Asia are placed in the genus Microtus (Carleton & Musser, ) together with the only representative of the entire Cricetidae family distributed in the African continent, the Cyrenaican vole.…”
Section: Introductionmentioning
confidence: 99%